Small Molecule Ice Recrystallization Inhibitors and Their Use in Methane Clathrate Inhibition - Tonelli, Devin L. (Université d'Ottawa / University of Ottawa, 2013)
Inhibiting the formation of ice is an essential process commercially, industrially, and medically. Compounds that work to stop the formation of ice have historically possessed drawbacks such as toxicity or prohibitively high active concentrations. One class of molecules, ice recrystallization inhibitors, work to reduce the damage caused by the combination of small ice crystals into larger ones. Recent advances made by the Ben lab have identified small molecule carbohydrate analogues that are highly active in the field of ice recrystallization and have potential in the cryopreservation of living tissue. A similar class of molecules, kinetic hydrate inhibitors, work to prevent the formation of another type of ice – gas hydrate. Gas hydrates are formed by the encapsulation of a molecule of a hydrocarbon inside a growing ice crystal. These compounds become problematic in high pressure and low temperature areas where methane is present - such as an oil pipeline. A recent study has highlighted the effects of antifreeze glycoprotein, a biological ice recrystallization inhibitor, in the inhibition of methane clathrates. Connecting these two fields through the synthesis and testing of small molecule ice recrystallization inhibitors in the inhibition of methane hydrates is unprecedented and may lead to a novel class of compounds.
Keywords: Clathrate; Ice Recrystallization; Carbohydrate Chemistry; Ice Recrystallization Inhibition; Amine Carbohydrates